Salinity reduces carbon assimilation and the harvest index of cassava plants (Manihot esculenta Crantz) - Jailson Lopes Cruz; Mauricio Antonio Coelho Filho; Eugenio Ferreira Coelho; Andrade Alves dos Santos (Acta Scientiarum. Agronomy, 2017)
This study was developed to evaluate the effects of salinity on the growth and gas exchange of cassava plants, cultivar Verdinha. The four concentrations of NaCl (mM) were as follows: 0, 20, 40, and 60. Under salinity, the lowest concentration of Na+ ions was observed in the tuberous roots; however, the dry matter of tuberous roots was reduced with an application of just 20 mM NaCl. The harvest index was reduced 50% with the highest salt concentration. Salinity reduced carbon assimilation (A), stomatal conductance (gs), transpiration, and the instantaneous water use efficiency. The correlation between gs and A was high and positive, showing that stomatal movement was one of the responsible for the lower A. Under salt stress, there was an increase in intercellular CO2 concentration, indicating the impairment of carbon metabolism. Based on the reduction of dry matter of the tuberous roots (reduction of 81% under 60 mM NaCl), it was concluded that cassava is sensitive to salinity. The growth of shoots and the absorbing roots were minimally affected by salinity, even in the situation where A was reduced; therefore, the sensitivity of cassava was related to the high sensitivity of the tuberous roots to the ionic and/or osmotic effects of salinity. Thus, tuberous roots can be the target organ in studies that aim to improve the tolerance of cassava to salinity.